Retinoic acid is abundantly detected in different depots of adipose tissue by SERS. (1st October 2016) - Perumal, Jayakumar; Sriram, Sandhya; Lim, Hann Qian; Olivo, Malini; Sugii, Shigeki
ABSTRACT: Retinoic acid (RA) is essential for early developmental processes and stem cell differentiation, but less is known about its contributions to adult tissues and stem cells including adipose tissue. We previously demonstrated that many genes involved in RA synthesis and downstream pathway are differentially expressed in adipose-derived stem cells (ASCs) from visceral fat compared to those from subcutaneous fat, leading to changes in their early adipogenic functions. In order to study potential contributions of RA in adipose tissue, we measured tissue RA levels using a technique based on surface-enhanced Raman spectroscopy (SERS). The data indicate heretofore underappreciated abundance of endogenous RA in mouse adipose tissue compared to other tissues and dynamic changes of RA concentrations after high fat diet feeding. Our results lay the foundation for further investigation on the functional role of RA in adipose tissue development and metabolism.